Factors associated with prolonged viral shedding in older patients infected with Omicron BA.2.2 - Weijie Zhong; Xiaosheng Yang; Xiufeng Jiang; Zhixin Duan; Wei Wang; Zhaoliang Sun; Wanghao Chen; Wenchuan Zhang; Jie Xu; Juan Cheng; Xiaoling Yuan; Yi Li (Frontiers Media S.A., 2023)
BackgroundThis study explores the risk factors associated with viral shedding time in elderly Chinese patients infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) omicron.MethodsParticipants infected with SARS-CoV-2 omicron were enrolled in a retrospective study, and divided into two groups according to shedding time (≥10 days, "late clearance group" and <10 days, "early clearance group").ResultsA total of 180 patients were enrolled in the study (88 early, 92 late), with a median viral shedding time of 10 days and a mean age of 77.02 years. Prolonged SARS-CoV-2 omicron shedding was associated with old age (p = 0.007), lack of vaccination (p = 0.001), delayed admission to hospital after onset of diagnosis (p = 0.001), D-dimer (p = 0.003), and methylprednisolone treatment (p = 0.048). In multivariate analysis, vaccination (OR, 0.319, 95% CI, 0.130-0.786, p = 0.013), Paxlovid (OR, 0.259, 95% CI, 0.104-0.643, p = 0.004), and time from onset of diagnosis to admission (OR, 1.802, 95% CI, 1.391-2.355, p = 0.000) were significantly associated with viral clearance.ConclusionsTime from onset of diagnosis to hospitalization, lack of treatment with Paxlovid, and lack of vaccination were independent risk factors in elderly Chinese patients infected with SARS-CoV-2 omicron for prolonged viral shedding.